2013
DOI: 10.5513/jcea01/14.3.1287
|View full text |Cite
|
Sign up to set email alerts
|

Live weight and body measurement of Hungarian Thoroughbred broodmares

Abstract: Live weights and 21 body measurements of 110 adult brood mares from Hungarian Thoroughbred broodmares were evaluated. Body measurements and some body measure indices were determined. One way ANOVA was used to compare the studs. Regression equations were developed to estimate the live weight from body measurements. The overall mean values of body measurements were as follows: live weight 542.0 kg, height at withers with stick 160.9 cm, height at withers with tape 168.8 cm, height of back 151.9 cm, height at rum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In this study, we evaluated factors affecting body conformation traits by measuring objective parameters. It was reported that the coefficients of variation were 2–8% in the Brazil Pantaneiro horse [13] and 2.1–6.7% in Hungarian Thoroughbred broodmares [3]. It was also reported that the coefficients of variation for croup height and croup width in the Pura Raza Espanola horse were 2.3 and 9.3%, respectively [17].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we evaluated factors affecting body conformation traits by measuring objective parameters. It was reported that the coefficients of variation were 2–8% in the Brazil Pantaneiro horse [13] and 2.1–6.7% in Hungarian Thoroughbred broodmares [3]. It was also reported that the coefficients of variation for croup height and croup width in the Pura Raza Espanola horse were 2.3 and 9.3%, respectively [17].…”
Section: Discussionmentioning
confidence: 99%
“…Variation coefficients of body conformation traits in the Brazilian Pantaneiro horses (MISERANI et al, 2002), Hungarian Thoroughbred broodmares (BENE et al, 2013) and Pura Raza Española horses (SÁNCHEZ et al, 2013) were 2% to 8%, 2.1% to 6.7%, and 2.3% to 9.3%, respectively. The results of the aforementioned studies corroborate those of this study.…”
Section: Nongenetic Factorsmentioning
confidence: 99%
“…According to individual authors, Kawareti et al (2017), we took all traits from left side of the horses. Bene et al (2013) in their work gave body measurements of Thoroughbred broodmares according to different authors, measured with stick. However, body measurements and reproductive characteristics, primarily gestation length, depend not only on the genotype but also on a significant number of non-genetic factors.…”
Section: Introductionmentioning
confidence: 99%